CAPITAL STRUCTURE AND CORPORATE PERFORMANCE OF LISTED HEALTHCARE COMPANIES IN MALAYSIA : Received: 21st October 2021; Revised: 09th February 2022, 11th February 2022, 13th February 2022; Accepted: 14th February 2022 - Lim, Wan Ching; Naysary, Babak (PEOPLE: International Journal of Social Sciences, 2022)
This study is focused on describing the dependent variable phenomenon under study which is corporate performance. The study will evaluate the influences of capital structure and the dimensions towards the corporate performance of listed healthcare companies in Malaysia. The nature of the investigation is quantitative based correlation design, and the purpose of this investigation is to determine the existence of the relationship between debt to total asset ratio, debt to total equity ratio, and long-term debt ratio of capital structure with the corporate performance of listed healthcare companies in Malaysia. This study setting is non-contrived as there are no changes made in the study setting and it is merely collecting data from secondary resources. The data will be randomly selected from the company’s annual report. The sample size of this study is 24 listed healthcare companies in Malaysia from the year 2018 to the year 2020. To determine the influences of capital structure and the relationship towards corporate performance by using appropriate statistical techniques. The findings indicated that DAR, DER, and LDR had a statistically significant linear relationship on ROE; whereas DAR, DER and LDR had no significant linear relationship on ROA.